The British Indian Army : Virtue and Necessity - Edited by Johnson, Robert, 1967- (Newcastle upon Tyne Cambridge Scholars, 2014)
The British Indian Army was a distinctive phenomenon, a curious combination of Western imperial and South Asian military cultures. It was first and foremost a military instrument for garrison duties, but it was rarely used in internal security and most of its history is concerned with expeditionary wars
Include Index
Keywords: Great Britain. Army. British Indian Army -- World War (1914-1918) -- India